Product-sound quality: A new aspect of machinery noise - BLAUERT, J.; JEKOSCH, U. (Archives of Acoustics, 1998)
Quality is an issue of current attention with regard to product-sound design and assessment as it has now been widely recognised that the quality of the sound that a product makes is a significant component of the consumers’ overall judgement on the product. This trivial fact has long been neglected by engineers and - much to their concern - they are now more and more pushed to take account of it in the product-development process. It is the aim of this article to provide the basis for a more differentiated view on product-sound quality than is currently common in the field. Special focus will be put on the process of perception and judgement in the context of quality assessment. It is hoped that engineers are encouraged to take on product-sound design and assessment as a generic engineering task.